KEBIJAKAN PENGEMBANGAN PERIKANAN HUHATE DI MALUKU - Stevanus Marelly Siahainenia (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2020)
Skipjack resources are quite potential in Maluku waters and are generally caught with pole and line. Skipjack is an important economic commodity with the aim of domestic and export markets, so it is expected to improve the welfare of the community. The purpose of this study is to formulate a pole and line fisheries development policy strategy in Maluku. The analytical method uses the SWOT approach technique and continued with AHP. Policy priorities for pole and line fisheries development in Maluku include: (1) optimal utilization of fishery resources; (2) empowering fishing communities; (3) government and private collaboration in the field of fisheries; (4) increasing business productivity; (5) market development through product quality improvement; (6) increasing capital assistance for business development; (7) strengthening the quality of fishermen's resources; and (8) supervision and law enforcement in the field of fisheries.